Revitalização urbana em Niterói : uma visão antropológica - Botelho, André Amud (2006)
This study meant to describe, in the light of anthropology s theory and method, the process and conflicts related to the diffused idea of a necessary revitalization in the downtown of Niterói, putting these process in the dialectic mechanism of creation-destruction-recreation of the world, proper to modernity, and so well explained by Marshall Berman, Walter Benjamin or Charles Baudelaire. This analysis also tried to oppose to the moribund condition, which the need of revitalizing bring to the neighborhood, the description of the diversity of uses and occupations in an area of collective use located in the downtown of Niterói, the Praça Jardim São João , spot chosen between many others of the town to appoint what kind of life (so criticized and morally refused) is specific to Niterói`s downtown.